مقاربة تاريخية ونظرية للواقع اللغوي للطفل الجزائري - مشطر حسين (جامعة الوادي - University of Eloued, 2021)
تشكل اللغة بعدا أساسيا من ابعاد الهوية الذاتية والثقافية، وهي حلقة وصل تربط بين ماضي الانسان وحاضره ومستقبله، كما تعتبر فضاء تفكيري واللسان المعبر عن المشاعر والعواطف، وحسب جاك بيرك اللغة لا تصلح للتواصل بل للوجود، ومن خلال هذه المقاربة نحاول في هذه المقالة تركيز التحليل على الوضع الهجين الذي يعيشه المتعلم نتيجة لضغط أنظمة لهجية محلية تزاحم نظام اللغة العربية الفصحي ،حيث تم تشخيص وضعية اللغة الام عند الطفل الجزائري من خلال ثلاث ابعاد الأول يتعلق بالمزاوجة بين الدارجة والفصحي و الثاني يتمثل في الثنائية اللغوية اما الاخير فهو التعددية اللغوية. وبتوظيف المنهج الاستقرائي تم بحث التداخل المعرفي بين المتغير التاريخي متمثلا في توظيف العامية في المدرسة الجزائرية ابان الحقبة الاستعمارية مع المتغير المعرفي التنظيري لكيفية اكتساب اللغة، في علاقتهما التفاعلية بين ثنائية الاسرة والمدرسة لان المحيط اللفظي للطفل يتكون من جميع الأشخاص الذين يحيطون ويتواصلون معه، وقد خلصنا الي انه لكي نحافظ على الامن اللغوي للطفل الجزائري الصحيح والفصيح يجب الاستثمار في المدرسة. Language is a fundamental dimension of the self and cultural dimensions of identity; which is a link between man's past, present and future ; it is also considered a space for my thinking and the tongue that expresses feelings and emotions, and according to Jack Burke, language is not suitable for communication, but for existence. Through this approach, we try in this article to focus the analysis on the hybrid situation that the learner lives because of the pressure of local dialect systems crowding out the classical Arabic language system. Where he was diagnosed with the status of the mother longue when the Algerian child through the first three dimensions of respect pairing between the colloquial language and the classical language, the second is bilingualism, while the latter is multilingualism. By employing the inductive approach, the cognitive overlap between the historical variable was examined represented in the employment of the colloquial in the Algerian school during the colonial era with the theoretical cognitive variable of how the language is acquired ,in their interactive relationship between the family and the school, because the verbal environment of the child consists of all the people who surround and communicate with him, and we concluded that in order to preserve the linguistic security of the correct and eloquent Algerian child, investment must be made in the school.
A historical and theoretical approach to the linguistic reality of the Algerian child.
مقال
Keywords: ازدواج اللهجات؛ الثنائية اللغوية؛ التعددية اللغوية؛ اللغة الام؛ استراتيجية التحيز اللغوي; diglossic, bilinguisme, plurilinguisme, Mother Language, Linguistic bias strategy